Factors influencing the release kinetics of drug nanocrystal-loaded pellet formulations. (May 2013) - Möschwitzer, Jan P.; Müller, Rainer H.
<x xml:space="preserve">Abstract</x> Context: This article discusses the downstream processing of nanosuspensions into oral solid dosage forms. Objective: Various factors influencing the release kinetics of various pellet formulations containing drug nanocrystals have been evaluated. The effects of binder types, drug content and pellet type on the in-vitro dissolution profiles were investigated. Materials and methods: Hydrocortisone acetate (HCA) was nanosized by using a piston gap homogenizer Micron Lab 40. The nanosuspension was admixed to various binder solutions based on chitosan chloride, polyvinyl alcohol, hydroxypropyl methylcellulose or polyvinylpyrrolidone (PVP) and sprayed on sugar beads using fluidized bed coating. For comparison, matrix cores have also been prepared using the extrusion-spheronization process. An enteric top coating was applied onto both pellet types. All pellet formulations have been tested In in-vitro dissolution studies. Results and discussion: HCA nanosuspensions were compatible with all binders tested except for PVP. Various suspensions could be successfully transferred into spray coated pellets as well as matrix cores including a top coating. The different binder types have influenced the stability of the nanosuspensions, the zeta potential of the drug nanocrystals as well as the dissolution profiles of the final solid dosage forms. Conclusion: Nanosuspensions can be easily processed into various pellet formulations. Spray coating with water-soluble binders is recommended for high dose drugs. This technology is also more variable with respect to the drug load In the final dosage form. Matrix cores can be beneficial for highly water-insoluble formulations, especially when only relatively low doses are needed.